The influence of the big five personality on performance with work engagement as intervening variable - Lugiani, Tigin; Apriandi, Devy Widya; Januar, Imelda; Sopiawadi, Mutqi (Proceeding International Conference on Accounting and Finance, 2024)
This study aims to test The Big Five Personality, performance, and work engagement are important parts of this study. This study aimed to determine the effect of the big five personality on performance with work engagement as an intervening variable for permanent employees in Sari Ater Hot Springs. The research method used in this study is a quantitative descriptive method with statistical methods multilinear regression test, t-test, and the coefficient of determination using the SPSS 27 program, this research also used the Sobel test to examine how much influence of the big five personality has and work engagement as a intervening variable on performance, the data collection method uses by distributing questionnaires to respondents with a sample consisting of 80 sari ater hot spring employees as respondent. The sampling technique used is proportionated random sampling. The results of this study show the big five personality influences performance, the big five personality influences work engagement, and work engagement influences performance. The result of the Sobel test shows that work engagement is proven to play a role in intervening the big five personality on performance. In this study work engagement is an intervening variable for the big five personality on performance.